(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aims to achieve a balance between one of the main economic objectives, represented by increasing economic growth rates and meeting the requirements of economic development, and maintaining environmental safety through reducing carbon emissions. This is proposed through a model that focuses, alongside the oil industry, on establishing industries based on petroleum derivatives as an alternative to exporting crude oil and natural gas as raw products. The model also seeks to strengthen and expand exports, then utilize the surplus foreign currency reserves to address economic challenges and imbalances. In addition, the study supports the establishment of carbon markets, encourages the cultivation of olive trees, promotes green education, and provides all the smart tools and means required in this field to ensure the preparation of generations that are aware of the importance of the environment and capable of consolidating the concepts of the green economy and sustainable development.